Simultaneous Assay of ρ-Coumaric Acid and Coumarin Co-encapsulated in Lipid-core Nanocapsules: Validation of an LC Analytical Method - Boschetti, Ticiane K.; de Oliveira, Edilene Gadelha; Rigo, Lucas Almeida; Coradini, Karine; Ruver Beck, Ruy Carlos (Current Pharmaceutical Analysis, 2019)
Background: Lipid-Core Nanocapsules (LNC) containing co-encapsulated ρ-coumaric acid and coumarin are under development. However, there is a lack of analytical methods to assay these bioactives in nanoformulations. Objective: The aim of this study was to validate an LC analytical method for the simultaneous determination of ρ-coumaric acid and coumarin in lipid-core nanocapsules. Methods: The mobile phase was composed of acetonitrile:water (40:60 v/v) adjusted to pH 4 and a C- 18 reversed-phase column was used. Both bioactives were detected at 275 nm. Specificity, linearity, range, precision and accuracy of the method were assessed, according to the official requirements. Results: Nanocapsules containing ρ-coumaric and coumarin had monomodal particle size distribution, spherical-shape and Z-average size of 207 ± 2 nm. LC method was specific, linear (5 to 30 μg.mL-1), precise (RSD < 5%) and accurate (97 - 103%). It was applied to assay the content and encapsulation efficiency of the bioactive substances in LNC, which were close to 0.5 mg.mL-1 and 72%, respectively. Conclusion: The proposed analytical method is reliable for the simultaneous assay of ρ-coumaric acid and coumarin in nanocapsules and can be further used in their development.
Keywords: Bioactives